Fintech and Entrepreneurship: An Assessment Model to Evaluate Policy Instruments for Fintech Adoption by Small and Medium Enterprises - Alassaf, Deemah; Daim, Tugrul; Dabic, Marina; Alzahrani, Saeed (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
Small and medium enterprises (SMEs) are the engines that drive economic development. However, they face inferior conditions and challenges when it comes to their access to broad financing channels. Hence, financial technologies (Fintech) solutions offer promising potential for improving SMEs' access to finance. While researchers and practitioners have been promoting Fintech as a potential financial safeguard for SMEs' needs, evidence shows an inadequate adoption rate of SMEs to such solutions and a lack of a comprehensive view of the Fintech adoption. Therefore, this research aims to provide a comprehensive examination of Fintech policy instruments and analyze their effectiveness in increasing the adoption of Fintech by SMEs through evaluating the essential policy targets impacting the adoption of Fintech and assessing their weights and priorities. This research is built upon a comprehensive literature review and experts' insights. The hierarchical decision modeling methodology is used to identify the relative importance of those factors proposing a policy evaluation tool to assess the effectiveness of policy instruments on increasing Fintech adoption. This research presents the identification of 17 distinct policy targets that fall within four main perspectives along with their relative weights. To test the practicality and value of the research, a case study of the policy instrument effectiveness, the Saudi Arabian regulatory sandbox, was conducted to illustrate how the model could be used to identify the policy instrument's actual performance in terms of influencing SMEs adoption of Fintech, identify the instrument's strengths and weaknesses, and offer recommendations on how to improve to increase the policy instrument's effectiveness in increasing the adoption of Fintech by SMEs.
Keywords: Instruments; Technological innovation; Entrepreneurship; Finance; Regulators; Government; Faces; Decision making in technology management; Fintech; small and medium enterprises (SMEs); technology assessment; technology entrepreneurship; TECHNOLOGY; FIRMS; SIZE; Business & Economics; Engineering